Hα LINE AS AN INDICATOR OF ENVELOPE PRESENCE AROUND THE CEPHEID POLARIS Aa (α UM i) - Usenko, I. A.; Miroshnichenko, A. S.; Klochkova, V. G.; Tavolzhanskaya, N. S. (Одеські астрономічні публікації, 2016)
We present the results of the radial velocity (RV ) measurements of metallic lines as well as Hα (Hβ ) obtained in 55 high-resolution spectra of the Cepheid α UMi (Polaris Aa) in 1994–2010. While the RV amplitudes of these lines are roughly equal, their mean RV begin to differ essentially with growth of the Polaris Aa pulsational activity. This difference is accompanied by the Hα core asymmetries on the red side mainly (so-called knifelike profiles) and reaches the value of 8–12 km/s in 2003 with subsequent decrease to 1.5–2 km/s. We interpret so unusual behaviour of the Hα line core as dynamical changes in the envelope around Polaris Aa.